The lower limb of Ardipithecus ramidus - Simpson, Scott W.; Levin, Naomi E.; Quade, Jay; Rogers, Michael; Semaw, Sileshi (American Journal of Physical Anthropology, 2019)
Keywords: dept.ant; peer-reviewed; ⛔ No DOI found

Postcranial fossils of Ardipithecus ramidus from Gona, Ethiopia - Simpson, Scott W.; Levin, Naomi E.; Quade, Jay; Rogers, Michael J.; Semaw, Sileshi (American Journal of Physical Anthropology, 2018)
Keywords: dept.ant; peer-reviewed; ⛔ No DOI found

Ardipithecus ramidus postcrania from the Gona Project area, Afar Regional State, Ethiopia. - Simpson, Scott W; Levin, Naomi E; Quade, Jay; Rogers, Michael J; Semaw, Sileshi (Journal of human evolution, 2019)
Functional analyses of the 4.4 Ma hominin Ardipithecus ramidus postcrania revealed a previously unknown and unpredicted locomotor pattern combining arboreal clambering and a form of terrestrial bipedality. To date, all of the fossil evidence of Ar. ramidus locomotion has been collected from the Aramis area of the Middle Awash Research Project in Ethiopia. Here, we present the results of an analysis of additional early Pliocene Ar. ramidus fossils from the Gona Project study area, Ethiopia, that includes a fragmentary but informative partial skeleton (GWM67/P2) and additional isolated manual remains. While we reinforce the original functional interpretations of Ar. ramidus of having a mixed locomotor adaptation of terrestrial bipedality and arboreal clambering, we broaden our understanding of the nature of its locomotor pattern by documenting better the function of the hip, ankle, and foot. The newly recovered fossils document a greater adaptation to bipedality in the Ar. ramidus ankle and hallux than previously recognized. In addition, a newly discovered scaphoid bone with a fusing os centrale provides further evidence about the nature of hominin hand evolution. Copyright © 2018 Elsevier Ltd. All rights reserved.
Keywords: *Fossils/ah [Anatomy & Histology]; *Hominidae/ah [Anatomy & Histology]; *Hominidae/ph [Physiology]; *Locomotion; Adaptation, Biological; Afar; Animals; Ardipithecus ramidus; Biological Evolution; Bipedality; Ethiopia; Fossils; Gona; Hominidae; Hominin; Locomotion; Pliocene; Postcrania; Skeleton; Skeleton/ah [Anatomy & Histology]; adaptation; anatomy and histology; animal; bipedalism; bone; cranium; dept.ant; evolution; fossil; hominid; locomotion; paleontology; peer-reviewed; physiology; skeleton

Isotopic evidence for plio-pleistocene environmental change at gona, ethiopia - Levin, Naomi E; Quade, Jay; Simpson, Scott W; Semaw, Sileshi; Rogers, Michael J (Earth and Planetary Science Letters, 2004)
A 4.5 Ma record of fluvial and lacustrine deposits is well exposed at Gona, in the Afar Depression of Ethiopia. We use isotopic values of pedogenic carbonate and fossil teeth to reconstruct Plio-Pleistocene environmental change at Gona. An increase in δ13C values of pedogenic carbonates since 4.5 Ma points to a shift from woodlands to grassy woodlands in the early Pliocene, -10.4 to -3.9‰ (VPDB), to more open but still mixed environments in the late Pleistocene, -3.0 to -1.4‰ (VPDB). This pattern is also seen in isotopic records elsewhere in East Africa. However, at 1.5 Ma the higher proportion of C4 grasses at Gona is largely a result of a local facies shift to more water-limited environments. The wide range of δ13C values of pedogenic carbonate within single stratigraphic levels indicates a mosaic of vegetation for all time intervals at Gona that depends on depositional environment. Elements of this mosaic are reflected in δ13C values of both modern plants and soil organic matter and Plio-Pleistocene soil carbonate, indicating higher amounts of C4 grasses with greater distance from a river channel in both the modern and ancient Awash River systems. δ18O values of pedogenic carbonates increase up-section from -11.9‰ in the early Pliocene to -6.4‰ (VPDB) in the late Pleistocene. The wide range of δ18O values in paleovertisol carbonates from all stratigraphic levels probably reflects short-term climate changes and periods of strong evaporation throughout the record. Based on the comparison between δ18O values of Plio-Pleistocene pedogenic carbonates and modern waters, we estimate that there has been a 6.5‰ increase in mean annual δ18O values of meteoric water since 4.5 Ma. δ18O values of pedogenic carbonate from other East African records indicate a similar shift. Increasing aridity and fluctuations in the timing and source of rainfall are likely responsible for the changes in δ18O values of East African pedogenic carbonates through the Plio-Pleistocene. © 2004 Elsevier B.V. All rights reserved.
Keywords: Africa; East Africa; Ethiopia; Gona; Isotopes; Paleoclimate; Paleosols; Pleistocene; Plio-Pleistocene; Pliocene; Sub-Saharan Africa; carbonate sediment; dept.ant; isotopic analysis; paleoenvironment; peer-reviewed; sediment chemistry

Fossil Cercopithecidae from the Early Pliocene Sagantole Formation at Gona, Ethiopia - Frost, Stephen R.; Simpson, Scott W.; Levin, Naomi E.; Quade, Jay; Rogers, Michael J.; Semaw, Sileshi (Journal of Human Evolution, 2020)
The Early Pliocene Sagantole Fm. in the Gona Project area, Afar State, Ethiopia, is noted for discoveries of the early hominin Ardipithecus ramidus. A large series of fossil cercopithecid primates dated to between 4.8 and 4.3 Ma has also been collected from these sediments. In this paper, we use qualitative analysis and standard dental and postcranial measures to systematically describe the craniodental remains and tentatively allocate postcrania to taxa where we are able to. We then use these data to compare these specimens to fossil assemblages from contemporary sites, interpret their paleobiology, and discuss implications for the paleoecology of the Gona Sagantole Fm. We recognize three cercopithecid species in the Gona Sagantole Fm. Pliopapio alemui makes up approximately two-thirds of the identifiable specimens; nearly all of the rest are allocated to Kuseracolobus aramisi, and a single molar indicates the presence of a second, somewhat larger but morphologically distinct papionin. Among the Early Pliocene cercopithecids from Gona are also a number of postcranial elements. None of the postcranial remains are directly associated with any of the cranial material. Nonetheless, some of the distal humeri and proximal femora can be tentatively allocated to either Pl. alemui or K. aramisi based on a combination of size, as the latter is approximately 50% larger than the former, and morphology. If these assignments are correct, they suggest K. aramisi was primarily arboreal and similar to most extant colobines, whereas Pl. alemui was more mixed in its substrate use, being more terrestrially adapted than K. aramisi, but less so than extant Papio or Theropithecus. Thus, we interpret the predominance of Pl. alemui over K. aramisi is consistent with a somewhat more open environment at Gona than at Aramis. © 2020 Elsevier Ltd
Keywords: Animals; Ardipithecus ramidus; Cercopithecidae; Ethiopia; Female; Fossils; Gona; Kuseracolobus; Life History Traits; Male; Paleobiology; Papio; Pliocene; Pliopapio; Primates; Theropithecus; anatomy and histology; animal; cranium; dentition; dept.ant; female; fossil; fossil assemblage; hominid; life history trait; male; paleobiology; paleoecology; peer-reviewed; physiology; qualitative analysis; taxonomy

Paleoenvironments of the earliest stone toolmakers, Gona, Ethiopia - Quade, Jay; Levin, Naomi E; Semaw, Sileshi; Stout, Dietrich; Renne, Paul R; Rogers, Michael J; Simpson, Scott W (Geological Society of America Bulletin, 2004)
Fluvio-lacustrine sediments of the Hadar and Busidima Formations along the northern Awash River (Ethiopia) archive almost three million years (3.4 to <0.6 Ma) of human evolution, including the earliest documented record of stone toolmaking at 2.5-2.6 Ma. This paper brings together sedimentologic and isotopic evidence for the paleoenvironmental context of early hominids from both formations, but with particular emphasis on the setting for the early toolmakers. The pre-2.92 Ma record (Hadar Formation) is characterized by low-gradient fluvial, paludal, and lacustrine deposition in an undissected topography most analogous to reaches of the modern middle Awash River near Gewane. The Gona area experienced repeated deep dissection and aggradation by the Awash River, starting between 2.92 and ca. 2.7 Ma and continuing through the top of the record at <0.6 Ma (Busidima Formation). Each aggradational succession is 10-20 m in thickness and fines upward from well-rounded conglomerates at the base to capping paleosols at the top. During this period the ancestral Awash represented by these fining upward sequences was dominantly meandering and flowed northeast, as it does today. Smaller channels tributary to the axial Awash system are also extensively exposed in the Busidima Formation. Compared to the axial-system conglomerates, the tributary channels transported finer, less mature volcanic clasts mixed with abundant carbonate nodules reworked from adjacent badlands. Stone artifacts (Oldowan; 2.6-2.0 Ma) at the oldest archaeological sites are only associated with the axial Awash system, in the bedded silts or capping paleosols of the fining upward sequences. The implements were made from rounded cobbles from the channels, but manufacture and use of the tools was always away from the channel bars, on the nearby sandy banks and silt-dominated floodplains. Archaeological sites higher in the record (Acheulian; <1.7 Ma) occur in similar axial river contexts, as well as along tributary channels further removed from artifact raw material sources. Mature paleosols in the Hadar and Busidima Formations are mostly pale to darkbrown Vertisols typified by abundant clay slickensides, pseudo-anticlinal and vertical fracturing, and carbonate nodules. Such calcic Vertisols are common in the region today, demonstrating that the paleoclimate over the past 3.4 m.y. has been semi-arid and strongly seasonal. Carbon isotopic results from pedogenic carbonates in the Vertisols allow reconstruction of the proportion of C3 plants (trees and shrubs) to C4 plants (grasses) through time. The δ 13C results from the Hadar Formation prior to 2.9 Ma range from -9.3‰ to -4.1‰, indicating a dominantly forested environment but with locally substantial (average 34%) grasses on the Awash floodplain. The δ13C values from soil carbonate in the lower Busidima Formation (2.7-1.6 Ma) increase (-6.5‰ to -2.7‰) in floodplain paleosols, indicating ∼ 50% average grass cover. Vertisols of the upper Busidima Formation (< 1.6 Ma) formed on gently sloping alluvial fans adjacent to the Awash floodplain and display even more positive δ13C values, up to -1.8‰, showing that grassland dominated the margins of the active Awash floodplain. © 2004 Geological Society of America.
Keywords: Africa; Awash; Axial flow; Carbon isotopes; Cenozoic; Deposition; Early hominids; East Africa; Eastern Hemisphere; Ethiopia; First stone tools; Gona; Human evolution; Oldowan; Paleoenvironment; Paleoenvironments; Rivers; Sediments; Sub-Saharan Africa; Tools; World; dept.ant; fluviolacustrine deposit; hominid; human activity; lithic fragment; paleoenvironment; tool use

Estimating sexual size dimorphism in fossil species from posterior probability densities - Sasaki, Tomohiko; Semaw, Sileshi; Rogers, Michael J.; Simpson, Scott W.; Beyene, Yonas; Asfaw, Berhane; White, Tim D.; Suwa (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Accurate characterization of sexual dimorphism is crucial in evolutionary biology because of its significance in understanding present and past adaptations involving reproductive and resource use strategies of species. However, inferring dimorphism in fossil assemblages is difficult, particularly with relatively low dimorphism. Commonly used methods of estimating dimorphism levels in fossils include the mean method, the binomial dimorphism index, and the coefficient of variation method. These methods have been reported to overestimate low levels of dimorphism, which is problematic when investigating issues such as canine size dimorphism in primates and its relation to reproductive strategies. Here, we introduce the posterior density peak (pdPeak) method that utilizes the Bayesian inference to provide posterior probability densities of dimorphism levels and within-sex variance. The highest posterior density point is termed the pdPeak. We investigated performance of the pdPeak method and made comparisons with the above-mentioned conventional methods via 1) computergenerated samples simulating a range of conditions and 2) application to canine crown-diameter datasets of extant known-sex anthropoids. Results showed that the pdPeak method is capable of unbiased estimates in a broader range of dimorphism levels than the other methods and uniquely provides reliable interval estimates. Although attention is required to its underestimation tendency when some of the distributional assumptions are violated, we demonstrate that the pdPeak method enables a more accurate dimorphism estimate at lower dimorphism levels than previously possible, which is important to illuminating human evolution. © 2021 National Academy of Sciences. All rights reserved.
Keywords: Animals; Bayes Theorem; Bayes theorem; Cuspid; Female; Fossils; Male; Models; Sex Characteristics; Statistical; animal; article; attention; canine tooth; controlled study; dept.ant; female; fossil; human; human experiment; intermethod comparison; male; nonhuman; peer-reviewed; primate; probability; sex difference; sexual characteristics; statistical model

Late Miocene hominin teeth from the Gona Paleoanthropological Research Project area, Afar, Ethiopia. - Simpson, Scott W; Kleinsasser, Lynnette; Quade, Jay; Levin, Naomi E; McIntosh, William C; Dunbar, Nelia; Semaw, Sileshi; Rogers, Michael J (Journal of Human Evolution, 2015)
Since 2000, significant collections of Latest Miocene hominin fossils have been recovered from Chad, Kenya, and Ethiopia. These fossils have provided a better understanding of earliest hominin biology and context. Here, we describe five hominin teeth from two periods (ca. 5.4 Million-years-ago and ca. 6.3 Ma) that were recovered from the Adu-Asa Formation in the Gona Paleoanthropological Research Project area in the Afar, Ethiopia that we assign to either Hominina, gen. et sp. indet. or Ardipithecus kadabba. These specimens are compared with extant African ape and other Latest Miocene and Early Pliocene hominin teeth. The derived morphology of the large, non-sectorial maxillary canine and mandibular third premolar links them with later hominins and they are phenetically distinguishable and thus phyletically distinct from extant apes. Copyright © 2014 Elsevier Ltd. All rights reserved.
Keywords: *Fossils/ah [Anatomy & Histology]; *Hominidae/ah [Anatomy & Histology]; *Tooth/ah [Anatomy & Histology]; Afar; Animals; Ardipithecus; Ardipithecus kadabba; Ardipithecus ramidus; Biological Evolution; Ethiopia; Fossils; Hominidae; Hominina; Late miocene; Miocene; Orrorin; Tooth; Western ethiopian escarpment; anatomy and histology; animal; anthropology; canid; dept.ant; evolution; fossil; hominid; morphology; peer-reviewed; tooth

2.6-Million-year-old stone tools and associated bones from OGS-6 and OGS-7, Gona, Afar, Ethiopia - Semaw, Sileshi; Rogers, Michael J; Quade, Jay; Renne, Paul R; Butler, Robert F; Dominguezrodrigo, Manuel; Stout, Dietrich; Hart, William S; Pickering, Travis Rayne; Simpson, Scott W (Journal of Human Evolution, 2003)
Keywords: Afar; Animalia; Bone fragments; Cutmarks; Earliest stone tools; Ethiopia; Gona; Hominidae; Mammalia; Ounda Gona; Pliocene; archaeological evidence; artifact; bone; dept.ant; peer-reviewed; tool use

Canine sexual dimorphism in Ardipithecus ramidus was nearly human-like. - Suwa; Sasaki, Tomohiko; Semaw, Sileshi; Rogers, Michael J.; Simpson, Scott W.; Kunimatsu, Yutaka; Nakatsukasa, Masato; Kono, Reiko T.; Zhang, Yingqi; Beyene, Yonas; Asfaw, Berhane; White, Tim D. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Body and canine size dimorphism in fossils inform sociobehavioral hypotheses on human evolution and have been of interest since Darwin’s famous reflections on the subject. Here, we assemble a large dataset of fossil canines of the human clade, including all available Ardipithecus ramidus fossils recovered from the Middle Awash and Gona research areas in Ethiopia, and systematically examine canine dimorphism through evolutionary time. In particular, we apply a Bayesian probabilistic method that reduces bias when estimating weak and moderate levels of dimorphism. Our results show that Ar. ramidus canine dimorphism was significantly weaker than in the bonobo, the least dimorphic and behaviorally least aggressive among extant great apes. Average male-to-female size ratios of the canine in Ar. ramidus are estimated as 1.06 and 1.13 in the upper and lower canines, respectively, within modern human population ranges of variation. The slightly greater magnitude of canine size dimorphism in the lower than in the upper canines of Ar. ramidus appears to be shared with early Australopithecus, suggesting that male canine reduction was initially more advanced in the behaviorally important upper canine. The available fossil evidence suggests a drastic size reduction of the male canine prior to Ar. ramidus and the earliest known members of the human clade, with little change in canine dimorphism levels thereafter. This evolutionary pattern indicates a profound behavioral shift associated with comparatively weak levels of male aggression early in human evolution, a pattern that was subsequently shared by Australopithecus and Homo. © 2021 National Academy of Sciences. All rights reserved.
Keywords: Animals; Australopithecus; Bayes Theorem; Bayes theorem; Biological Evolution; Cuspid; Ethiopia; Female; Fossils; Hominidae; Humans; Male; Models; Pan paniscus; Phylogeny; Sex Characteristics; Theoretical; adult; aggression; anatomy and histology; animal; article; canine tooth; cladistics; classification; dept.ant; evolution; female; fossil; hominid; human; male; mandibular canine; maxillary canine; nonhuman; peer-reviewed; phylogeny; sex difference; sexual characteristics; theoretical model

Co-occurrence of Acheulian and Oldowan artifacts with Homo erectus cranial fossils from Gona, Afar, Ethiopia. - Semaw, Sileshi; Rogers, Michael J; Simpson, Scott W; Levin, Naomi E; Quade, Jay; Dunbar, Nelia; McIntosh, William C; Caceres, Isabel; Stinchcomb, Gary E; Holloway, Ralph L; Brown, Francis H; Butler, Robert F; et al. (Science advances, 2020)
Although stone tools generally co-occur with early members of the genus Homo, they are rarely found in direct association with hominins. We report that both Acheulian and Oldowan artifacts and Homo erectus crania were found in close association at 1.26 million years (Ma) ago at Busidima North (BSN12), and ca. 1.6 to 1.5 Ma ago at Dana Aoule North (DAN5) archaeological sites at Gona, Afar, Ethiopia. The BSN12 partial cranium is robust and large, while the DAN5 cranium is smaller and more gracile, suggesting that H. erectus was probably a sexually dimorphic species. The evidence from Gona shows behavioral diversity and flexibility with a lengthy and concurrent use of both stone technologies by H. erectus, confounding a simple "single species/single technology" view of early Homo. Copyright © 2020 The Authors, some rights reserved; exclusive licensee American Association for the Advancement of Science. No claim to original U.S. Government Works. Distributed under a Creative Commons Attribution NonCommercial License 4.0 (CC BY-NC).
Keywords: *Biological Evolution; *Fossils; *Hominidae; *Skull/ah [Anatomy & Histology]; Animals; Archaeological site; Behavioral diversity; Biodiversity; Biological Evolution; Co-occurrence; Ethiopia; Fossils; Hominidae; Hominidae/ah [Anatomy & Histology]; Hominidae/cl [Classification]; Hominins; Homo erectus; Humans; Paleontology; Single species; Skull; anatomy and histology; animal; classification; dept.ant; evolution; fossil; hominid; human; paleontology; peer-reviewed; skull